Electrodiagnostic Studies Role in Diagnosis and Management of Thoracic Outlet Syndrome - Mohammad Reza Kalantar Motamedi 1, Niki Tadayon2, Mohammad Karimian3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Thoracic outlet syndrome (TOS) is caused by the compressive effect on brachial plexus or subclavian vessels at the thoracic outlet. The symptoms are usually neurologic, arterial or venous or the combination of them. Method: From these patients we chose 70 patients whom underwent surgery (resection of first rib ,with neurolysis with trans axillary approach) and we had the complete data on EMG -NCV and could follow postoperative course and were completely satisfied by the operation and their symptoms was relieved according the quick DASH Questionnaire and thereby the diagnosis of TOS was proved by the result. Result: The electro diagnostic tests of 6 patients (1.5%) were completely normal. The lower trunk symptoms which should be more frequent in TOS was purely present in 7.1%. Fibrillation and fasciculation along the course of ulnar nerve was present in 10% of cases. The middle trunk abnormal motor NCV was the pure pathology in2.9%. Fibrillation and fasciculation along the course of median nerve (abductor policis berevis) 2.4% and for Brachioradialis (radial nerve) NCV was abnormal in 1.8%. Conclusion: To prove this fact, we selected only the patients who were completely satisfied by the operation and their symptoms was relieved according the quick DASH Questionnaire and thereby we were sure that the diagnosis of TOS has been correct. Retrospectively we evaluated the electrodiagnostic findings in these patients.